From a cosmopolitan fraternity to a loyalist institution: Freemasonry in British North America in the 1780s–1790s. Issue 3 (3rd July 2019) - Huskins, Bonnie
ABSTRACT: British Freemasons accommodated the revolutionary politics of the eighteenth-century Atlantic world until the 1790s, when the British waged war against revolutionary France and suppressed internal radicalism and associations they defined as seditious. British Grand Lodges reoriented to overt displays of loyalty, such as adopting royal patrons, and consolidating their authority over Freemasonry. This transformation from an elastic and cosmopolitan fraternity to a loyalist institution was highly embattled. This essay examines this shift within "Hiram Lodge No. 17" in Saint John, New Brunswick. Lodge members became embroiled in political conflicts in the colony's first election in 1785. A decade later, members sparred with Masonic officialdom, after Nova Scotia's provincial grand lodge adopted the anti-revolutionary turn of British Grand Lodges. It clamped down on fractious lodges, including Hiram Lodge, a case demonstrating the complex relationship between fraternal organizations and the dynamic political culture of the late eighteenth- and early nineteenth-century Atlantic world.